Intercultural Communication in Confessional Legal Relations (Common and Particular in Russia and Japan) - S. Takahashi; E. I. Arinin; I. V. Pogodina (Концепт: философия, религия, культура, 2021)
The study of particularities of regional cross-country images of confession and intercultural communication as well as the semantic image surrounding these concepts is vital in today’s social life. The article analyzes denotations and connotations of the terms confession and intercultural communication in the Russian and Japanese sociocultural contexts from the point of view of a new research discourse — glocal religious studies with the focus on vernacular specifics of religiosity in Russia and Japan. The case study methodology includes description and analysis of how various views on certain aspects of religiosity correlate. It makes possible to adjust the theoretical understanding of the problem and weigh it against the variety of real-life communicational practices. The article investigates the complexity and dramatism of communication between members of the ingroup and others. The study bases on the materials from the history, media and academic discourses where in the internal and external of particular communities in the given historic circumstances may not only vary significantly, but also be intentionally marked to divide one from the other. Sometimes this demarcation takes a form of stigmatization that label one’s perspective as not-true or lawless. The paper describes two major types of culture: the first one (ethnocentrism in terms suggested by M. Bennet) derives from the idea that other’s statements are sealed and cannot be translated thus must be destroyed. The second type — ethnorelativism — comes from the idea of affinity and openness. It is presumed that taking one a different perspective and accepting diversity is empowering and gives start to an intercultural dialogue. Common and particular are the two basic viewpoints on any identity, when both positive and negative promotes understanding. The phenomenon of unity as similarity of indistinguishable (like grains of sand) on the one hand, and systemic unity of the different (like people) on the other hand, are considered within the framework of distancing extralinguistic social facts from the term that stand for them. The latter shown as special imaginary unities and descriptions of autopoietic systems.